Postpartum Depression: A Closer Look at Treatment with Zuranolone - Brudniak, Katarzyna; Garbino, Karolina; Czyczerska, Magdalena; Szuścik, Antoni; Gadżała, Katarzyna; Przygodzka, Sabina; Mach, Maciej; Rutkiewicz, Maciej (Quality in Sport, 2025)
Postpartum depression (PPD) is a severe mood disorder that affects approximately 1 in 7 women and 1 in 10 men, often occurring in the first year after childbirth. Its etiology is multifactorial, including hormonal changes, genetic predisposition, and environmental stressors, though its true prevalence is likely underestimated due to stigma and underreporting. Untreated PPD can have long-term consequences for maternal-child relationships, child development, and maternal health, including increased suicide risk. The condition remains underdiagnosed and undertreated due to stigma and systemic barriers to care. Zuranolone, an oral neuroactive steroid and positive allosteric modulator of GABA-A receptors, has recently garnered attention as a novel therapeutic option with the potential to target these underlying pathophysiological mechanisms. Aim of the study: The aim of this study is to provide a comprehensive review of the therapeutic efficacy, safety, and pharmacological characteristics of Zuranolone in the treatment of postpartum depression (PPD), with focusing particularly on its mechanism of action, pharmacokinetics and clinical trial outcomes. Materials and methods: A systematic literature review was conducted using PubMed and other medical databases. Keywords included "postpartum depression," "zuranolone," "GABA-A modulators,". Data from clinical trials, reviews, and pharmacological studies were analyzed. Conclusions: Zuranolone has provided significant efficacy with a very rapid onset of action in the reduction of symptoms in postpartum depression and long-term improvements observed over several weeks. Its mechanism of action, targeting GABAergic dysregulation, offers a novel therapeutic pathway for addressing postpartum psychiatric disorders. Future longitudinal studies are required to explore its long-term impact on maternal mental health.